Bystander Attitudes to Prevent Sexual Assault: A Study of College Students in the United States, Japan, India, Vietnam, and China. Issue 9 (21st November 2016) - Kamimura, Akiko; Trinh, Ha Ngoc; Nguyen, Hanh; Yamawaki, Niwako; Bhattacharya, Haimanti; Mo, Wenjing; Birkholz, Ryan; Makomenaw, Angie; Olson, Lenora M.
Abstract : College women are at a high risk of sexual assault. Although programs that aim to change bystander behaviors have been shown to be potentially effective in preventing sexual assault on campuses in the United States, little is known about bystander behaviors outside of the United States. The purpose of this study was to explore and compare factors affecting bystander behaviors regarding sexual assault intervention and prevention among undergraduate students in the United States, Japan, India, Vietnam, and China. A total of 1, 136 students participated in a self-reported survey. Results demonstrate substantial variations across countries. Bystander behaviors are associated with multilevel factors, including gender, knowledge of individuals who have experienced a sexual assault, and knowledge about campus or community organizations.